Mapping The Potential Of Village Agricultural Social Economic Improvement Efforts In Lubuk Kertang Village Kecamatan Berandan Barat Kabupaten Langkat - Mailina Harahap; Gustina Siregar; Fetra Venny Riza (JASc (Journal of Agribusiness Sciences), 2020)
Increasing the utilization of village resource potential is a part that cannot be separated from sustainable agriculture and rural development (Sustainable Agriculture and Rural Development). The various resources found in the village are production factors to produce a number of agricultural products or commodities. How much the value of the resources used will determine the yield of agricultural commodities both quantitatively and qualitatively. The ability of the village to provide various infrastructure and facilities and utilize the village's potential optimally is largely determined by the village's ability to fulfill funding for village development. The research method is a participatory approach, namely the Participatory Rural Appraisal (PRA) technique. Data analysis was statistically descriptive and qualitative. The potential of Lubuk Kertang village, among others; Resources and agricultural potential of rainfed lowland rice, ponds. potential natural resources of mangrove forests, Purun plants, human resources, artificial resources, social and institutional resources. The mapping of agricultural-based village potential can be grouped into the agricultural sector, which consists of livestock, rice farming, horticulture, mangrove forests and coastal areas (aquaculture and capture fisheries) which are closely related and mutually supportive for their sustainability.